Analisis Konten Maharah Kitabah dalam Buku Ajar Bahasa Arab Kementerian Agama - Hanif Syukron; Mohammad Samsul Ulum; Mamluatu Solihah (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
Writing skills are one of the most important skills in Arabic, in fact this skill is the last achievement that every student must achieve in learning Arabic. Therefore, a book learning media is needed that can support these achievements to be in accordance with the established planning. For this reason, this study aims to analyze the learning content of the Ministry of Religion's Arabic textbook writing skills in 2020 to measure the level of conformity of this skill learning content with the standards for compiling Arabic textbooks. This study uses a descriptive-analytical method using a qualitative approach to find the level of conformity of the book with the standards for compiling Arabic textbooks. The results that have been achieved in this study are that of the seven points of writing skills content preparation standards set by Abdurrahman Fauzan, there are three corresponding points and the other 3 pounds are still not owned by the content of the book, while one point still needs to be developed again.